2022
DOI: 10.7759/cureus.28975
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diet and Gut Microbiome in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a chronic demyelinating condition of the central nervous system (CNS) characterized by immune-mediated damage to the myelin sheath of nerve cells. Genetic and environmental factors are believed to play a significant role. Unfortunately, the knowledge of therapeutic modalities in MS remains very limited, necessitating the need for novel therapeutic strategies. In the previous decade, there has been an influx of studies on the gut microbiome and its link to various neurological conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The majority of previous studies are case-control studies, and it was challenging to ascertain both the exposure and outcome. Furthermore, it should be considered that in prospective studies, the association between sphingomyelin abundance and the gut microbiota abundance could be in uenced by several confounding variables, including age, environment, dietary habits and lifestyle [14,15] , and given that these factors are di cult to control for in observational studies, their effect on the association needs to be considered. Therefore, causal inference between sphingomyelin and gut microbiota abundance is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous studies are case-control studies, and it was challenging to ascertain both the exposure and outcome. Furthermore, it should be considered that in prospective studies, the association between sphingomyelin abundance and the gut microbiota abundance could be in uenced by several confounding variables, including age, environment, dietary habits and lifestyle [14,15] , and given that these factors are di cult to control for in observational studies, their effect on the association needs to be considered. Therefore, causal inference between sphingomyelin and gut microbiota abundance is limited.…”
Section: Introductionmentioning
confidence: 99%
“…al. [2] 2022 Review Similar to severe ophthalmic ictus, CRAO too is an ophthalmic emergency. Yet, presently, no therapy that guidelines have approved is available.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being comparable to the severity of brain stroke, there is presently no evidence for therapy that guidelines have approved. The "standard" therapies still used today include methylprednisolone, intravenous (IV) acetazolamide, mannitol, systemic pentoxifylline, sublingual isosorbide dinitrate, hyperbaric oxygen (O 2 ) therapy, anterior chamber paracentesis, globe compression, and ocular massage [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the diet is made of many components ingested together, so there are likely significant interactions. Peculiar dietary patterns may influence the activity and progression of MS differently [ 18 , 22 ]. In fact, Noormohammadi M. et al showed that adhering to the MIND diet (Mediterranean-DASH Intervention for Neurodegenerative Delay) may be an effective strategy for MS prevention: according to research, the polyphenols found in vegetables and beans may inhibit the production of proinflammatory factors, so the use of plant-based meals and the reduction of animal-derived or high-saturated fat foods consumption is encouraged [ 23 ].…”
Section: Introductionmentioning
confidence: 99%